Enfance et vulnérabilité. Ce que la politisation de l'enfance fait au concept de vulnérabilité - Tal Piterbraut-Merx
The analysis of the place conferred on childhood in the theories of care has a methodological and critical virtue: that of revealing the problematic implications of a certain use of the concept of vulnerability. The strategic use of the reference to the child within these theories is structured around a twofold idea: 1. early childhood can provide evidence of fundamental vulnerability, and 2. the mother-child relationship allows the child's dependency to be dealt with. This double thesis must be critically analyzed. To this end, I propose a paradigm shift: it is no longer a question of focusing on the dyadic mother-child relationship but of analyzing the socio-political condition of the group of children. The assignment of the vulnerability of certain social groups will then become graspable as the result of a process of institutional production. This new methodology, which takes a critical look at the use of the concept of vulnerability, is attentive to the extra-philosophical circulation of philosophical terms and draws lessons from them.